Transformers - Rugoff, Ralph (New York : Independent Curators Incorporated, 1994)
Durham, Jimmie ; Flanagan, Bob ; Rose, Sheree ; Gomez-Peña, Guillermo ; Holzer, Jenny ; Kelley, Mike ; McCarthy, Paul ; Komar & Melamid ; Ledray, Charles ; Ligon, Glenn ; Marclay, Christian ; McCarthy, Paul ; Morimura, Yasumasa ; Opie, Catherine ; Piper, Adrian ; Sherman, Cindy ; Deavere Smith, Anna ; Vasiman, Meyer ; Velarde, Kukuli ; Wilson, Fred
Transformers: A traveling exhibition organized and circulated by Independent Curators Incorporated, New York, 1994
boek